Polyaniline Nanoskein: Synthetic Method, Characterization, and Redox Sensing - Yoochan Hong; Hyun Soo Kim; Taeha Lee; Gyudo Lee; Ohwon Kwon (Nanoscale Research Letters, 2020)
Abstract Polyaniline nanoskein (PANS), which have polyaniline nanofibers, was developed. PANS was formulated via sequential extracting, heating, and swelling processes. The compositions of PANS have been analyzed using X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and Brunauer–Emmett–Teller analysis, and the results of which indicate that PANS is composed of solely organic materials. Moreover, PANS has been shown convertible absorbance characteristics according to surrounding acidic environments, and using these characteristics, the possibility of PANS for sensing of surrounding redox state changes is presented.